EFL Instruction in the 21st century: Meeting the challenges - Kateryna Lizak; Лізак Катерина; Lizák Katalin („RIK-U” Kft., 2018)
Abstract. At present, in our fast changing world nobody denies the necessity to study at least one foreign language and, in this particular case, it is the much favoured English. English seems to have been adopted as the language of globalization these days. Thus, the study of English is of special importance and relevance. Likewise, Ukraine is no exception in this regard and aiming to find some effective ways for teaching English, special attention has been paid to various methods of its teaching over the last years. Since no method met the high expectations with regard to their application, no breakthrough was achieved in foreign language instruction either, in the present study it is suggested that emphasis shall be shifted from the method of teaching to the material of instruction, i.e. from how to tech to what to teach.
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
Keywords: Ukraine’s External Independent Evaluation; level of proficiency; proficiency trend; knowledge; vocabulary instruction